Retinal atrophy and markers of systemic and cerebrovascular severity in homozygous sickle cell disease. Issue 6 (November 2022) - Martin, Gilles C.; Brousse, Valentine; Connes, Philippe; Grevent, David; Kossorotoff, Manoelle; Da Costa, Lydie; Bourdeau, Hélène; Charlot, Keyne; Boutonnat-Faucher, Bénédicte; Allali, Slimane; De Montalembert, Mariane; Bremond-Gignac, Dominique; et al.
Introduction: While paramacular retinal atrophy (PRA) is known to be found in 48% of eyes of adults and 42% of eyes of children with homozygous SCD (SS-SCD), the aim of this study is to assess the association between PRA and red blood cell (RBC) deformability, hematological markers and brain imaging abnormalities in SS-SCD. Methods: This study is a subset of DREAM2, a prospective observational study performed between August 2015 and August 2016. Children (5–17 years) with SS-SCD and no history of large vessel vasculopathy, were included. Ophthalmological characteristics including visual acuity, fundus examination, OCT of central and temporal retina (with several retinal thickness measurements) were explored in relation with RBC deformability (ektacytometry), hematological and biochemical (hemolysis parameters), and neurological (cerebral oxygenation estimated by Near Infrared Spectroscopy, brain magnetic resonance imaging) investigations. Results: 17 children (5 boys; mean age: 13 years) with complete ophthalmological investigations were included in the analysis; 8 exhibited PRA. RBC deformability was found to be significantly lower in children with PRA for measurements made at 1.69 Pa (0.16 a.u ± 0.02 vs 0.21 a.u ± 0.03, p = 0.02) and above, as well as cerebral oxygenation (59.25% ± 9.9 vs 71.53% ± 4.9, p = 0.02). A significant positive correlation was found between temporal retinal thickness and hemoglobin level (ρ = 0.65, p = 0.007), hematocrit (ρ = 0.53, p = 0.04) and RBC deformability at 3 Pa (ρ = 0.75, p = 0.005) and above. Conclusions: These results suggest that PRA could be an early marker of systemic severity and cerebral oxygenation in SCD. Whether it could help predicting cerebral vasculopathy requires further investigations.